问题 解答题
计算:
(1)
1
3
+
1
4
1-
3
5
×
7
12
=
(2)
0.5-
1
8
÷
5
12
6
1
5
-4
3
4
=
(3)
5
2
5
-1
2
3
3
8
+
5
12
×
7
10
=
(4)
1-2
1
5
÷3
1
7
1
1
4
+
2
5
=
(5)
(18-16
3
7
)×2.8
2.75+1
5
6
=
(6)
1÷0.35
(
1
3
+
1
4
)×1
3
7
=
答案

(1)

1
3
+
1
4
1-
3
5
×
7
12

=

7
12
1-
7
20

=

7
12
13
20

=

7
12
×
20
13

=

35
39

(2)

0.5-
1
8
÷
5
12
6
1
5
-4
3
4

=

1
2
-
1
8
×
12
5
6
4
20
-4
15
20

=

1
2
-
3
10
29
20

=

(
1
2
-
3
10
)×20
29
20
×20

=

4
29

(3)

5
2
5
-1
2
3
3
8
+
5
12
×
7
10

=

5
6
15
-1
10
15
3
8
+
7
24

=

56
15
2
3

=

56
15
×
3
2

=

28
5

(4)

1-2
1
5
÷3
1
7
1
1
4
+
2
5

=

1-
11
5
×
7
22
1
5
20
+
8
20

=

1-
7
10
33
20

=

3
10
×
20
33

=

2
11

(5)

(18-16
3
7
)×2.8
2.75+1
5
6

=

(18-
115
7
)×2.8
2
3
4
+1
5
6

=

50.4-46
55
12

=4.4×

12
55

=0.96.

填空题
单项选择题